Distribution patterns of the family Solieriaceae (Gigartinales, Rhodophyta) in Mexico - Hernández, Oscar; Dreckmann, Kurt M.; Núñez Resendiz, María Luisa; Sentíes, Abel (Instituto de Ecología, A.C., 2021)
Background and Aims: Solieriaceae is a very diverse family of red algae, widely distributed in tropical and temperate areas of the world. In Mexico, there are 21 of the 94 current species, which represents 23% of the diversity worldwide. Despite the knowledge of the diversity and distribution of the species of this family in Mexico, its biogeographic aspects are still unknown, fundamental for the understanding of the arrangement and evolution in the geographic space of any taxonomic group. The objective of this study was to identify and describe the distribution patterns of the Solieriaceae species in Mexico, through a Cladistic Analysis of Distribution and Endemism (PAE-CADE), to discuss the processes that have given rise to them; and based on this, provide evidence that contributes to future conservation proposals that involve these organisms.Methods: By defining quadrants of 2° latitude by 2° longitude in the Atlantic and Pacific oceans, a presence/absence matrix was constructed, with which a PAE-CADE analysis was performed.Key results: Two large areas of congruence were defined: the Pacific ocean with three nested areas, and the Atlantic ocean with four nested areas; all defined by the presence of one or more restricted species. Likewise, a biotic convergence in the Pacific ocean and an area of endemism in the Campeche Bank were detected.Conclusions: It is recognized that the Mexican coasts are composed of nested congruent areas with an intrinsic biotic complexity, i.e., by areas with different affinity and biogeographic origin. However, the incorporation of phylogenetic information to this kind of study will allow it to be integrated into the evolutionary biogeographic scheme.